2021
DOI: 10.3389/fnbeh.2021.634157
|View full text |Cite
|
Sign up to set email alerts
|

Marked Mild Cognitive Deficits in Humanized Mouse Model of Alzheimer’s-Type Tau Pathology

Abstract: Hyperphosphorylation and the subsequent aggregation of tau protein into neurofibrillary tangles (NFTs) are well-established neuropathological hallmarks of Alzheimer’s disease (AD) and associated tauopathies. To further examine the impact and progression of human tau pathology in neurodegenerative contexts, the humanized tau (htau) mouse model was originally created. Despite AD-like tau pathological features recapitulated in the htau mouse model, robustness of behavioral phenotypes has not been fully establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
(36 reference statements)
2
7
0
Order By: Relevance
“…In the present study, analyzing hTau mice at one year of age, we detected oligomerization of hyper-phosphorylated Tau, but not yet aggregation of the protein. Consistent with the late onset of AD-like Tau pathology in this particular hTau mouse model 69 , these observations likely reflect early disease conditions. In addition, reduced hTau expression due to a shortening of the transgene array over nineteen years of breeding might contribute to this effect 70 .…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, analyzing hTau mice at one year of age, we detected oligomerization of hyper-phosphorylated Tau, but not yet aggregation of the protein. Consistent with the late onset of AD-like Tau pathology in this particular hTau mouse model 69 , these observations likely reflect early disease conditions. In addition, reduced hTau expression due to a shortening of the transgene array over nineteen years of breeding might contribute to this effect 70 .…”
Section: Discussionsupporting
confidence: 76%
“…Overall, these data showed that female ePet1 hTauP301L mice have deficits in cognitive function when compared with female controls, while males do not show differences in spatial working memory when assessed at this time point. Spatial working memory deficits have been demonstrated in mouse models of AD with amyloid or tau pathology. Moreover, in addition to the higher prevalence of AD in female sex, cognitive impairment associated with AD manifests earlier in women than in men. , Additionally, women have higher levels of tau pathology across numerous brain regions, indicating greater vulnerability of the female sex to tau deposition and accelerated cognitive decline in the earlier stages of the disease . Taken together, we show that 5-HT neuron-specific hTauP301L expression in females results in impaired cognitive decline, while spatial working memory is spared in male mice with 5-HT neuron tau pathology.…”
Section: Resultsmentioning
confidence: 63%
“…Similar effects have also been observed in hiPSC‐derived neurons, which in addition exhibit changes in the AIS but do not show impairments in neuronal activity 100,189,190 . The expression of all six human TAU isoforms from an artificial chromosome in murine Mapt KO background resulted in increased dendritic localization of TAU, TAU hyperphosphorylation and aggregation, memory deficits, and neuronal loss 191–194 . These phenotypes are likely caused by the imbalance between 3R and 4R expression observed in these animals, which is also associated with several tauopathies 191–194 (see the TAU isoforms in tauopathies section).…”
Section: The Effect Of Tau Depletion and (Re‐)expression Of (Individu...mentioning
confidence: 57%